Happiness: a review - Ferraz, Renata Barboza (2007)
BACKGROUND: Happiness is a basic emotion characterized by a positive emotional state, with feelings of well-being and pleasure, associated with a perception of sucess and a coherent and lucid comprehension of the world. Recently, several researchers have been involved in the elucidation of the relationship between happiness and mental health. OBJECTIVE: Critically review the scientific literature concerning the topic happiness and its contributions to mental health and to psychiatry. METHODS: Systematic review of the literature through the MedLine database, using the uniterms: happiness, mental health, well-being, positive psychology, resilience, optimism, gratitude, quality of life, positive emotions and personality. RESULTS: Variables such as origin, physical and mental health, religiosity and certain psychological characteristics are positively associated with happiness. There is no evidence suggesting that age, gender, marital status, wealthiness or the occurrence of external factors (favorable or not) significantly associate with happiness. CONCLUSION: Happiness is a predominantly subjective phenomenon, subordinated to psychological and socio-cultural traits much more than to external factors. The identification of these factors is particularly useful when applied to subjects that are more predisposed to mental disorders, favoring the development of prevention approaches, which have potential repercussion in the social and occupational areas.